Redesain Logo ‘Hadimu Home Bakery’ Sebagai Identitas Visual Pada Usaha Kue di Kota Bandung - Larashati, Chintiya (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
The redesign of the ‘Hadimu Home Bakery’ logo aims to strengthen the visual identity of one of the cake businesses in Bandung City and raise the brand’s image among the public. ‘Hadimu Home Bakery’ is a business that sells various kinds of cakes in the city of Bandung. ‘Hadimu Home Bakery’ was founded by Hadi Mukhayyar in 2016 by selling various types of cakes such as donuts, bread, pudding and other cakes. ‘Hadimu Home Bakery’ has a visual identity that is not yet represented so that it can affect the brand identity of the business. Therefore, a redesain of the logo for ‘Hadimu Home Bakery’ was carried out. The design method used is Design Thinking which consists of five non-linear stages, namely Empathize, Define, Ideate, Prototype, and Test. The data analysis method uses SWOT analysis (Strengths, Weakness, Opportunities, Threats). The main media is a logo with Graphic Standard Manual (GSM), while the supporting media are neon boxes, shop window stickers, packaging, aprons an banners. The final design results are then tested on the client, designer, and target audience based on aspects of color, font readability, and layout arrangement. The overall design of the logo is used to communicate a message which is expected to necome the positioning of the ‘Hadi Home Bakery’ brand.